2017
DOI: 10.1016/j.cbpa.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerial hypoxia and temperature on pulmonary breathing pattern and gas exchange in the South American lungfish, Lepidosiren paradoxa

Abstract: The South American lungfish Lepidosiren paradoxa is an obligatory air-breathing fish possessing well-developed bilateral lungs, and undergoing seasonal changes in its habitat, including temperature changes. In the present study we aimed to evaluate gas exchange and pulmonary breathing pattern in L. paradoxa at different temperatures (25 and 30°C) and different inspired O levels (21, 12, 10, and 7%). Normoxic breathing pattern consisted of isolated ventilatory cycles composed of an expiration followed by 2.4±0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Overall, groups had a higher ABF after the 2 week acclimation to 30°C, especially at 20% oxygen availability. This may be due to hypoxia being exacerbated at higher temperatures due to a reduction in dissolved oxygen or elevated metabolic rate, which may have increased oxygen demand ( Breitburg et al, 2018 ; da Silva et al, 2017 ; Graham, 1997 ). Wang and Lin (2018) compared ABF under hypoxia alone, temperature alone, and then both stressors combined and found that ABF was highest at the most extreme temperature and hypoxia combination.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, groups had a higher ABF after the 2 week acclimation to 30°C, especially at 20% oxygen availability. This may be due to hypoxia being exacerbated at higher temperatures due to a reduction in dissolved oxygen or elevated metabolic rate, which may have increased oxygen demand ( Breitburg et al, 2018 ; da Silva et al, 2017 ; Graham, 1997 ). Wang and Lin (2018) compared ABF under hypoxia alone, temperature alone, and then both stressors combined and found that ABF was highest at the most extreme temperature and hypoxia combination.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in temperature is a combined systemic/environmental factor that stimulates air-breathing behavior in fishes because it increases the demand for O 2 in the tissues and requires increased O 2 delivery (Johansen et al, 1970;Rahn et al, 1971;Horn and Riggs, 1973;Graham and Baird, 1982;Glass et al, 1986;Johnston and Dunn, 1987;McMahon and Burggren, 1987;Smatresk, 1988;Clarke and Johnston, 1999;Geiger et al, 2000;Silva et al, 2017). Indeed, warming also lowers O 2 solubility in water, which reduces aquatic P O2 and additionally contributes to stimulate air-breathing behavior (Rahn, 1966;Johansen et al, 1970;Graham and Baird, 1982;McMahon and Burggren, 1987).…”
Section: Systemic Factorsmentioning
confidence: 99%
“…Electrophorus electricus exhibits no change in air-breathing frequency during aquatic hypoxia while Trichogaster trichopterus exhibits an increase) but not among sarcopterygians (aquatic hypoxia does not change air-breathing frequency in Lepidosiren paradoxa, Protopterus aethiopicus and Protopterus dolloi) Sanchez et al, 2001a;Perry et al, 2005a). It is conceivable that obligate sarcopterygians do not possess externally oriented O 2 chemoreceptors in the gills (Lahiri et al, 1970;Perry et al, 2005a;Silva et al, 2017). However, the actinopterygian and sarcopterygian species just cited, as well as the obligate air-breathing teleosts C. argus and Monopterus cuchia, show an increase in air-breathing frequency when exposed to aerial hypoxia, which may have been triggered by hypoxaemia through internally oriented chemoreceptors or by external chemoreceptors that monitor the P O2 of air in the ABO Lomholt and Johansen, 1974;Glass et al, 1986;Sanchez et al, 2001a;Zaccone et al, 2003Zaccone et al, , 2006Perry et al, 2005a;Silva et al, 2011Silva et al, , 2017.…”
Section: Environmental Factorsmentioning
confidence: 99%
See 2 more Smart Citations